2012
DOI: 10.1159/000337344
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadism in Patients with Sickle Cell Disease: Central or Peripheral?

Abstract: There is conflicting evidence in the literature on the etiology of hypogonadism in patients with sickle cell disease (SCD). A cross-sectional study was done to determine whether hypogonadism in male patients with SCD is due to primary testicular failure or secondary pituitary/hypothalamic dysfunction and assess the association between hypogonadism and serum ferritin levels. Hormonal assessment for serum concentrations of testosterone, follicle stimulating hormone (FSH) and luteinizing hormone (LH) was done for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 18 publications
1
44
2
Order By: Relevance
“…As adults, men with sickle-cell anaemia had significantly higher mean LH and FSH levels than controls and similar testosterone levels. These results contrast with the literature, since studies have shown low testosterone in adult men with sickle-cell anaemia, with gonadotropin levels that may reflect both hypogonadotropic hypogonadism and as hypergonadotropic 2,23 . A previous study found significantly lower testosterone averages in the sickle-cell anaemia group than in controls, but with similar averages of LH and FSH24.…”
Section: Discussioncontrasting
confidence: 99%
“…As adults, men with sickle-cell anaemia had significantly higher mean LH and FSH levels than controls and similar testosterone levels. These results contrast with the literature, since studies have shown low testosterone in adult men with sickle-cell anaemia, with gonadotropin levels that may reflect both hypogonadotropic hypogonadism and as hypergonadotropic 2,23 . A previous study found significantly lower testosterone averages in the sickle-cell anaemia group than in controls, but with similar averages of LH and FSH24.…”
Section: Discussioncontrasting
confidence: 99%
“…However, up to 24% of men with SCD may develop hypogonadism, a clinical syndrome associated with poor testosterone production, infertility, ED, and poor libido. 3 Clinical characteristics include sparse facial, pubic, and axillary hair and small testicular size. Clinical laboratory findings are low testosterone levels with variable follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels.…”
Section: Fertility In Menmentioning
confidence: 99%
“…4 Possible underlying pathophysiologic mechanisms of hypogonadism include disruptions in the hypothalamic-pituitary-gonadal axis leading to primary testicular failure. However, studies are inconsistent as to whether primary testicular failure 5,6 or secondary hypothalamic-pituitary dysfunction 3,4,[7][8][9] is the cause. A recent report found low serum testosterone levels in 8 of 34 men with SCD and all 8 had low FSH and LH levels, suggesting a central mechanism.…”
mentioning
confidence: 99%
“…Hypogonadism, a condition linked with infertility, poor testosterone production, poor libido and erectile dysfunction, develops in up to 24% of men with SCD [14]. Patients show sparse facial, axillary and pubic hair and small testicular size.…”
Section: Hypogonadismmentioning
confidence: 99%
“…The possible pathophysiologic mechanisms of hypogonadism are disruption in the hypothalamic-pituitary-gonadal axis, which leads to primary testicular failure [16,17], or secondary hypothalamic-pituitary dysfunction [14,15,18,19].…”
Section: Hypogonadismmentioning
confidence: 99%